ANALISIS DAMPAK LINGKUNGAN JOGJA PLAZA MALL (KAJIAN DAMPAK EKONOMI) - Prawoto, Nano (Jurnal Ekonomi & Studi Pembangunan, 2006)
This research studies the environmental impact of investment activity especially the project Jogja Plaza Mall. The environmental impact that studied is social and economic analysis with issues such us changes in infrastructure of goody distribution network, changes in local government income, changes in tax and distribution, changes in society income, and loss of social economic environment. The result of this research is the positive impact of the project more than negative impact of it, so the project of Jogja Plaza Mall can be accepted